Clinical Profile and Predictors of Posterior Reversible Encephalopathy Syndrome at Tertiary Care Hospital, Peshawar: Clinical Profile and Predictors of Posterior Reversible Encephalopathy Syndrome - Khan, Huma; Humza, Arbab; Haroon; Nassery, Ahmad Nasir; Khan, Nisar Ahmad (Pakistan Journal of Health Sciences, 2025)
Posterior Reversible Encephalopathy Syndrome is an acute neurological condition characterized by reversible subcortical vasogenic edema, often presenting with seizures, headache, visual disturbances, and altered mental status. Objectives: To evaluate the clinical profile, risk factors, radiological findings, and outcomes of Posterior Reversible Encephalopathy Syndrome patients at a tertiary care hospital in Peshawar. Methods: This prospective cohort study was conducted at Northwest General Hospital and Research Center, Peshawar, from January 2023 to March 2025. Ninety patients diagnosed with Posterior Reversible Encephalopathy Syndrome through clinical presentation and Magnetic Resonance Imaging confirmation were enrolled using non-probability consecutive sampling. Data on demographics, risk factors, symptoms, imaging, outcomes, and length of hospital stay were collected and analyzed. Descriptive analysis of the study was performed through SPSS version 25.0. Results: Among 90 patients, 61 (67.8%) were females, 29 (32.2%) were males. The mean age was 35.92 ± 3.16 years. Seizures (70%), headache (56.7%), and altered mental status (54.4%) were the most common symptoms. Hypertension (53.3%) and postpartum eclampsia (50.8% of females) were the leading risk factors. Magnetic Resonance Imaging showed parieto-occipital/cerebellar involvement in 74.4% and bilateral lesions in 96.7%. Most patients (92.2%) recovered and were discharged, while 7.8% passed away. Conclusions: Posterior Reversible Encephalopathy Syndrome is more prevalent in young females with underlying hypertension or postpartum complications. Early recognition and management can result in favorable outcomes. This study highlights the importance of timely diagnosis to prevent irreversible damage.